The perioperative management of geriatric patients in transplantation surgery—clinical, immunological, and translational considerations - Knoedler, Leonard; Boroumand, Sam; Hinze, Christopher A.; Knoedler, Samuel; Lellouch, Alexandre G.; Maheta, Bhagvat J.; Iske, Jasper; Panayi, Adriana C. (Frontiers in Transplantation, 2025)
Transplant surgery encompasses two primary branches: solid organ transplantation (SOT) and vascularized composite allotransplantation (VCA). As the global population ages, elderly transplant patients become a more pressing clinical challenge. Elderly transplant recipients require specialized care that addresses their unique needs, including increased comorbidities and frailty. Despite the growing recognition of these challenges, there is a paucity of studies that synthesize the current knowledge on this patient cohort, from immunological changes over translational challenges to tailored clinical care. This review highlights the individual needs of elderly transplant patients, emphasizing the importance of understanding their clinical profiles to develop specialized perioperative management strategies. The clinical need for tailored therapeutic concepts contrasts with the current lack of established, integrated care models specifically designed for older adults undergoing SOT and VCA. Overall, future research is warranted to provide individualized and cross-disciplinary care models for aging transplant patients and broaden the access to transplant surgery for this patient population.